2018
DOI: 10.3126/njr.v7i1-2.19365
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thyroid Nodule by Sonographic Features

Abstract: Introduction:  The thyroid is an endocrine gland situated in the infrahyoid compartment of neck in a space outlined by muscle, trachea, esophagus, carotid arteries and jugular veins. Though nodular thyroid disease is relatively common, thyroid cancer is rare and accounts for less than 1% of all malignancies indicating that overwhelming majority of thyroid nodules are benign. The purpose of this study was to assess the sonographic characteristics in a solitary thyroid nodule and predict  risk of malignancy.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In this study the prevalence of thyroid nodules was 88% out of 111 cases. Higher prevalence was seen in the study done by Khadka et al 10 In the study done by Ahmed et al 11 the prevalence was only 25.1%. The total benign cases in this study were 86 (87.7%) and malignant cases were 32 (32.65%).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this study the prevalence of thyroid nodules was 88% out of 111 cases. Higher prevalence was seen in the study done by Khadka et al 10 In the study done by Ahmed et al 11 the prevalence was only 25.1%. The total benign cases in this study were 86 (87.7%) and malignant cases were 32 (32.65%).…”
Section: Discussionmentioning
confidence: 73%
“…The total benign cases in this study were 86 (87.7%) and malignant cases were 32 (32.65%). Among 66 patients in Khadka et al's study, 10 there were 56 benign nodules and only six malignant nodules were noted. The malignant cases were seen among females than males in this study and female gender was associated with presence of nodule.…”
Section: Discussionmentioning
confidence: 91%
“…Like Reading et al , we found that the echo pa ern method for thyroid nodules is highly sensi ve and specific to the presence of benignity. In previous studies, the malignant risk of mixed echogenic nodules ranged from 2.3% to 21,22 17.6%. Our malignant rate is within this range.…”
Section: Discussionmentioning
confidence: 92%
“…[8,9,10] Higher malignancy rate (22.9 %) was found in our study while other studies showed a lower prevalence rate of malignant nodules of 9.2-13%. [11,12,13] The mean age of a patient with benign and malignant nodules was 52.37 years and 51.44 years respectively. There was no significant statistical relationship between age and sex of patient and malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The colloid nodule was the most common benign nodule and papillary carcinoma was the most common malignant nodule as found in another study. [12] Three patients with papillary carcinoma had nodal metastasis at presentation. Similar to a study by Ewid et…”
Section: Discussionmentioning
confidence: 99%